Geodiversity as part of Heritage Rivers: The Example of São Francisco, River of National Unity - Along the Stretch its River Source to the Casca d’Anta Waterfall - Oliveira, Carmélia Kerolly Ramos de; Amorim Castro, Paulo de Tarso; Ruchkys, Úrsula de Azevedo; Pereira, Diamantino Manuel Insua; de Sordi, Michael Vinicius (Anuário do Instituto de Geociências, 2021)
Rivers are key parts of geodiversity and have special proximity with society. Hence, river heritage is characterized by uncommon rivers with singular aspects of geodiversity, historical and cultural values, ecological and landscape elements of high scenic quality. In such context, the present study aimed to identify the set of elements or places of interest which could be used to recognize river heritage based on geodiversity values along a 17 km stretch between São Francisco river headwaters and the Casca d’Anta waterfall within Canastra Range National Park (Minas Gerais State - Brazil). Here, seven elements of river heritage were recognized: i) landscape set of the Canastra Range; ii) São Francisco historic headwater; iii) Curral de Pedras; Casca d’Anta waterfall; v) Nesting area of the Mergus octosetaceus; vi) diamond mining; vii) the Canastra cheese. The identified elements of river heritage highlight the scientific, ecological, cultural, historic and touristic/economic importance of the analyzed. stretch Moreover, such elements illustrate need for improvement of the existing legislations and more effective instruments of river management and river conservation.